2013
DOI: 10.1088/0004-637x/766/2/78
|View full text |Cite
|
Sign up to set email alerts
|

Gala: An Automatic Tool for the Abundance Analysis of Stellar Spectra

Abstract: GALA is a freely distributed Fortran code to derive automatically the atmospheric parameters (temperature, gravity, microturbulent velocity and overall metallicity) and abundances for individual species of stellar spectra using the classical method based on the equivalent widths of metallic lines. The abundances of individual spectral lines are derived by using the WIDTH9 code developed by R. L. Kurucz. GALA is designed to obtain the best model atmosphere, by optimizing temperature, surface gravity, microturbu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
106
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 34 publications
0
106
0
Order By: Relevance
“…The chemical abundances of Fe and Na have been derived with the package GALA (Mucciarelli et al 2013b) by matching measured and theoretical equivalent widths (EWs) of a set of unblended lines. EWs and RVs have been measured with the code DAOSPEC (Stetson & Pancino 2008), automatically launched by using the package 4DAO (Mucciarelli 2013), which allows a visual inspection of all the performed Gaussian fits.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical abundances of Fe and Na have been derived with the package GALA (Mucciarelli et al 2013b) by matching measured and theoretical equivalent widths (EWs) of a set of unblended lines. EWs and RVs have been measured with the code DAOSPEC (Stetson & Pancino 2008), automatically launched by using the package 4DAO (Mucciarelli 2013), which allows a visual inspection of all the performed Gaussian fits.…”
Section: Discussionmentioning
confidence: 99%
“…This parametrisation value is calculated by GALA by varying the best value found around the local minimum. This method and their respective equations are described in detail in Mucciarelli et al (2013). In our sample, the resulting errors are found to be σ T eff = 245 ± 99 K and σ ξ = 0.29 ± 0.11 km s −1 .…”
Section: Stellar Parametersmentioning
confidence: 94%
“…Most likely, the observed uncertainty associated with the initial stellar parameters is not caused by GALA itself, but by the inability to optimise the entire grid of parameters simultaneously in the bulge. Were a larger number of FeI and Fe II lines available in our spectra, the final scatter on stellar parameters would converge to less than 50 K in T eff and 0.09 in log g as described in Mucciarelli et al (2013) thus decreasing the relatively large scatter in [Fe/H] observed in Fig. 3.…”
Section: Stellar Parametersmentioning
confidence: 96%
See 2 more Smart Citations